AICCRA Internship Program: Pause and Reflect Report - ACDI/VOCA; International Water Management Institute (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The overall objective of the internship program is to expose university students and/or graduates to practical skills necessary for gainful employment and entrepreneurship over a period of 2 to 6 months. By employing interns, EDGE will address SMEs’ critical gaps and build their capacities to diversify their networks, increase the quality of their products, enhance their visibility, and identify new markets, which in turn, should increase SMEs’ sales, profits, and access to finance opportunities.